Insights into the Low‐temperature Synthesis of LaCoO3 Derived from Co(CH3COO)2via Electrospinning for Catalytic Propane Oxidation. Issue 2 (24th December 2019) - Zheng, Yingbin; Feng, Xiaoshan; Lin, Daifeng; Wu, Enhui; Luo, Yongjin; You, Yufeng; Huang, Baoquan; Qian, Qingrong; Chen, Qinghua
Summary of main observation and conclusion: A series of electrospun LaCoO3 perovskites derived from CoX2 (X = CH3 COO –, NO3 – ) were prepared and investigated for total propane oxidation. It is shown that pure rhombohedral perovskite LaCoO3 from Co(CH3 COO)2 can be obtained at a relatively low temperature, 400 °C, benefitting from the complexation effect of CH3 COO – . On the other hand, CH3 COO – can accelerate the complete decomposition of polymer. The low‐temperature process can protect LaCoO3 nanoparticles from growing up. As a result, Co(CH3 COO)2 ‐derived catalysts exhibit better propane oxidation activity than the ones suffered the same thermal treatment by using Co(NO3 )2 . XPS and H2 ‐TPR analysis provide that there is subtle change in Co 3+ /Co 2+ on bulk/surface of Co(CH3 COO)2 ‐derived catalysts prepared at different temperatures, giving rise to similar propane oxidation activities. Moreover, the result of cyclic stability test over 400 °C obtained catalyst shows little deactivation, demonstrating a good thermal stability. Our study can provide a feasible route for energy‐saving synthesis of LaCoO3 catalyst applied in the catalytic oxidation of volatile organic compounds (VOCs). Abstract : The bifunctional roles of CH3 COO – (complexation effect and decreasing temperature of PVP complete decomposition) are utilized to synthesize LaCoO3 perovskites at a low‐temperature 400 °C.